Making a mobile physical education gym to enhance and monitor the interest of pre-school children in physical activities - Petrović, Marija M.; Stanišić, Irena R. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2023)
Тhe aim of the paper is to examine the contribution of the constructed device, props and the new mobile gym to children`s interest in their use in physical activities. Both parents and pre-school teachers took part in the creation of the mobile gym and its equipment. They provided all the necessary material needed for making the following: ladders, beanbags, hula hoops, skipping ropes, cubes, mats, bowling pins, balance bar. This research included 55 children (30 boys and 25 girls). The research was carried out by monitoring the children and their interest in the provided props during the period of 3 weeks. The first pieces of props (5 of them) were introduced in the first week. In the second and the third week the pieces of props for which the children showed less interest were removed and new were introduced. Parents, teachers and children filled in the interviews. The research was carried out successfully. The results showed which props were more and which less interesting to children. Also, in general, children showed great interest in a new mobile gym and physical education (P.E.) props.